Penatalaksanaan Fisioterapi Pada Kasus Post Orif Fraktur 1/3 Ulna Distal Sinistra Di RSUD Sragen - Indriyani, Khoiriyah Nisa', Wahyuni, S.Fis., Ftr., M.Kes (2015)
Background: fracture is a loss of continuity of bone, joint cartilage, epiphyseal cartilage, either total or partial fracture can occur due to failure of the bone to withstand the pressure, especially the pressure to bend, twist, and pull. Problem physiotherapy obtained is impairment presence of spasms in the muscles bicep and tricep, presence of tenderness in muscles bicep, tricep, around the incision scars, pain in the joints elbow motion and wris, A decrease in muscle strength, LGS The limitation of the left elbow. The role of physiotherapy in reducing pain, decrease spasms, increase the LGS, Improve the ability of ADL Methods: the methods using is giving Infrared (IR) and exercise therapy, to evaluate the methods used by the VDS pain, muscle strength with MMT, LGS with Goneometer and ADL ability to UEFS. Objectives: above methods to understand the benefits of infrared therapy modalities, massage, exercise therapy to decrease pain, penurunkan spasm, increase LGS, peningktan muscle strength, increase the ability of ADL Results: After treatment for 6 times the therapy showed a decrease in pain, spasm reduction, improvement of LGS, increase muscle strength, increase the ability of ADL. Conclusion: infra red and massage can reduce pain, spasms in the case. Exercise therapy can improve the LGS, muscle strength and functional ability